Ante-Litteram One Health in India - Nadal, Deborah (Lagoonscapes, 2022)
Historical research on One Health is offering interesting information about the development of this concept within human and animal health institutions and professions. In contrast, little is known about whether and how local communities have discussed – in their own terms – and managed One Health issues. This paper presents three examples of community-led debate and action on One Health in India: the eco-religion of Bishnois, the collapse of the vulture population, and plastic pollution in cows’ bodies. More research from the social sciences and the humanities is necessary to understand and learn from the dynamics of multispecies entanglements at the local level.